Rusunawa as an Urban Living Space: Sociospatial Perspective - Aprilia C. P. Putri; Raphaella D. Dwianto (Jurnal Indonesia Sosial Teknologi, 2024)
This research examines the factors influencing Low-Cost Rental Flats (Rusunawa) residents to settle for extended periods in Jakarta. Previous studies have focused on the satisfaction levels of Rusunawa residents in remaining permanent tenants to sustain their livelihoods. Such an approach overlooks the issue that the development of Rusunawa has been merely targeted towards the quantity of Rusunawa and the physical completeness of the building, neglecting other non-physical factors that encourage Rusunawa residents to settle in these flats. We argue that the residents' comfort in residing in Rusunawa for prolonged durations is influenced by non-physical factors (social, cultural, economic, and political) that form a socio-spatial environment conducive for the flat residents. Gottdiener's (2015) socio-spatial approach supports the idea that signs and symbols of urban communities have become the identity for various urban issues arising from industrialization. This study was conducted in Rusunawa Sindang Koja, North Jakarta, and managed by Perum Perumnas. It employed a mixed-method research approach with data collection through questionnaires and in-depth interviews. The research findings indicate that non-physical factors such as social, economic, and cultural play a crucial role in an individual's decision to reside in Rusunawa, with the presence of family and social relationships being the primary determinants.